Histologic types of gastric cancer among migrants from the former Soviet Union and the general population in Germany: what kind of prevention do we need? - Jaehn, Philipp; Winkler, Volker (European journal of gastroenterology & hepatology, 2016)
Objective The incidence of gastric cancer (GC) is high among migrants from Eastern Europe and Asia, but a detailed picture of disease characteristics is missing. Our study examined the incidence of histologic types among resettlers from the former Soviet Union and the general population in Germany to draw conclusions on risk factors and possible prevention strategies. Methods Between 1990 and 2009, all GC diagnoses among a cohort of 18 619 resettlers residing in the Saarland were identified in the Saarland Cancer Registry database. Age-standardized incidence rates (ASRs) of the entire Saarland population and standardized incidence ratios (SIRs) of resettlers compared with the Saarland population were calculated for types according to Laurén. In addition, ASRs and SIRs were modeled using Poisson’s regression to investigate time trends. Results The ASR of intestinal GC in the Saarland population decreased over time, whereas the ASR of diffuse GC remained unchanged. Resettlers’ incidence of intestinal GC was elevated among men [SIR: 3.04, 95% confidence interval (CI): 2.05-4.50] and women (SIR: 2.78, 95% CI: 1.61-4.79), whereas diffuse GC was elevated only among women (SIR: 1.98, 95% CI: 1.07-3.69). No time trends for SIRs could be observed in regression analysis. Conclusion Different trends of diffuse GC incidence in Germany and the USA underline the importance of environmental risk factors. The continuously elevated risk of GC among male resettlers is probably associated with risk factors affecting exclusively the intestinal type such as a low intake of fruit and vegetables and heavy alcohol consumption. Future prevention programs for resettlers should include dietary measures.
Gesehen am 18.12.2018